2021
DOI: 10.1097/md.0000000000027580
|View full text |Cite
|
Sign up to set email alerts
|

The combination therapy of subtenon triamcinolone acetonide injection and intravitreal brolucizumab for brolucizumab-related intraocular inflammation

Abstract: Rationale: Brolucizumab is a novel anti-vascular endothelial growth factor agent with clinical trials demonstrating excellent efficacy for neovascular age-related macular degeneration (AMD) in both visual and anatomic outcomes. However, there is concern of intraocular inflammation (IOI), and we propose concurrent subtenon triamcinolone acetonide (STTA) to prevent IOI. Patient concern: A 73-year-old man was treated with aflibercept for neovascular AMD in his right eye. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…This study's treatment interval significantly extended from the first to the last interval at 12 months (from 6.15 ± 2.40 to 6.87 ± 2.92, p = 0.045). Several studies have reported the efficacy of brolucizumab for refractory exudative AMD in short-term results in the real-world [41,49,[56][57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study's treatment interval significantly extended from the first to the last interval at 12 months (from 6.15 ± 2.40 to 6.87 ± 2.92, p = 0.045). Several studies have reported the efficacy of brolucizumab for refractory exudative AMD in short-term results in the real-world [41,49,[56][57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…In phase 3 clinical trial of HAWK/HARRIER, intravitreal administration of (6.0 mg/0.05 mL) brolucizumab demonstrated similar visual gains to and better morphological improvement than the intravitreal administration of (2.0 mg/0.05 mL) aflibercept [35,36]. Although there remain safety concerns including intraocular inflammation (IOI), retinal vasculitis, and retinal vascular occlusion after intravitreal administration of brolucizumab, there is mounting evidence regarding incidence, treatment, and prophylaxis of intraocular inflammation [37][38][39][40][41][42][43][44][45][46]. Though these data from animal experiments and clinical trials suggest the possible advantage of brolucizumab over other anti-VEGF agents, few data reveal the efficacy of switching to brolucizumab from other anti-VEGF agents for neovascular AMD with persistent exudation, including SRF and IRF, despite multiple intravitreal injections.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Treatment with corticosteroids in the early phase has reportedly been proposed for patients with IOI after IVbr. 17 , 19 In the current case, we were able to perform early intensive treatment with STTA due to the prompt recognition of IOI showing an LFP value of 51.2 pc/ms. We were also able to monitor the efficacy of STTA based on the reduction in the LFP value to 30.3 pc/ms after 3 days and 17.9 pc/ms after 2 weeks from STTA.…”
Section: Discussionmentioning
confidence: 74%
“…IOI is well known to potentially occur after IVbr. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 Although IOI has been reported to occur in 4.6% of patients after injections in the HAWKS and HARRIER studies, it tends to be seen more frequency in Japanese patients by approximately 15% to 20%. 15 , 18 , 23 We should be alert for the occurrence of IOI and promptly diagnose early-phase IOI should it develop after the use of brolucizumab.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation